Screening for BRCA1 and BRCA2 mutations among French‐Canadian breast cancer cases attending an outpatient clinic in Montreal. (5th June 2013) - Ghadirian, P; Robidoux, A; Nassif, E; Martin, G; Potvin, C; Patocskai, E; Younan, R; Larouche, N; Venne, A; Zhang, S; Royer, R; Narod, SA
<x xml:space="preserve">Abstract</x> Study subjects were French‐Canadian women with ductal carcinoma in situ (DCIS) or invasive breast cancer (incident or prevalent) who were treated and followed at a single breast cancer clinic affiliated with the Research Center of University of Montreal (CRCHUM), who were either aged less than 50 years at diagnosis or who were 50 years or older and with at least two affected first‐ or second‐degree relatives. Subjects were tested for six founder mutations (three in BRCA1 and three in BRCA2); 1093 eligible cases were tested. Of these, 56 women (5.1%) were mutation carriers, including 43 BRCA2 carriers and 13 BRCA1 carriers. The prevalence of mutations was 5.3% for unselected women aged 50 and less and was 4.6% for familial cases over age 50. The prevalence of mutations was 3.3% for women with DCIS and was 5.3% for women with invasive cancer. It is rational to offer genetic testing to all French‐Canadian women diagnosed recently or in the past with either DCIS or invasive breast cancer before age 50 or with familial breast cancer above age 50.